Theoretical Review of Financial Management, Capital Markets, and Financial Institutions in the Digital Economy Era - Uswatun Khasanah; Muchriana Muchran; Nurul Khotimah (CV. AFDIFAL MAJU BERKAH, 2025)
The development of digital technology has brought significant changes in the field of finance, including financial management, capital markets, and financial institutions. This study aims to conduct a theoretical review of how basic financial concepts adapt and evolve in the era of the digital economy. The method used is a qualitative literature study with content analysis of various academic sources and relevant official reports. The results of the study indicate that digitalization affects financial management through automation and data-based decision making, changes the structure of the capital market with the emergence of digital assets and new trading platforms, and demands the transformation of financial institutions in dealing with digital risks and competition. This study concludes that classical financial theory needs to be expanded and adjusted to be able to explain the dynamics of modern finance influenced by digital technology. The main contribution of this study is to build an integrative theoretical framework that connects traditional financial theory with digital innovation as a foundation for contemporary financial research and practice.